2006
DOI: 10.1017/s0012162206001174
|View full text |Cite
|
Sign up to set email alerts
|

Dislocation of the hips in children with bilateral spastic cerebral palsy, 1985–2000

Abstract: The aim of this study was to assess the rate of hip dislocation at different ages in children with bilateral spastic cerebral palsy attending special schools in southern Derbyshire, UK, between 1985 and 2000. The medical notes of 110 individuals (68 males, 42 females) were obtained. They were divided into four groups according to the Gross Motor Function Classification System (GMFCS). We determined whether or not their hips were dislocated at the ages of 5, 10, and 15 years, and the kind of surgery performed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…After full text review, 15 papers remained. 1,[5][6][7][8]17,[22][23][24][25][26][27][28][29][30] A search of the reference lists of these articles, along with other key papers in the area, identified a further 24 potentially relevant articles. All of these newly sourced articles were excluded after application of inclusion and exclusion criteria to the full text.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After full text review, 15 papers remained. 1,[5][6][7][8]17,[22][23][24][25][26][27][28][29][30] A search of the reference lists of these articles, along with other key papers in the area, identified a further 24 potentially relevant articles. All of these newly sourced articles were excluded after application of inclusion and exclusion criteria to the full text.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies also supported the need for surveillance at a young age. 5,26 Cases of displacement occurring from 8 months of age have been reported, 5 as has dislocation before 2 years of age. 28 No data were found that would assist in differentiating a congenital or neurogenic hip displacement in this population.…”
Section: Review 811mentioning
confidence: 99%
“…The prevalence of hip dysplasia in cerebral palsy varies from 2% to 60%, with higher prevalence among children who are quadriplegic or nonambulatory, or have severe spasticity [110][111][112]. In cerebral palsy, the risk for subluxation or [113].…”
Section: Epidemiologymentioning
confidence: 99%
“…In the most severely impaired, non-ambulatory children, the incidence may be as high as 80% [11,15]. While children with CP are born with enlocated hips, progression to hip displacement is demonstrated in some children with CP from a very early age [13,14,16]. Hip surveillance programs and appropriately-timed interventions improve outcomes at skeletal maturity [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Although the final outcome of early intervention at skeletal maturity is not clear [17,18], early risk assessment might enable earlier referral for those children who may benefit from preventative intervention [19]. As clinical assessment of hip range of motion is a poor predictor of risk, several radiological and clinical measures are used to diagnose and monitor hip subluxation [13,16,17,19]. While functional disability, pain [20] and impaired ambulatory weight-bearing [12,16,18,19] are associated with risk of hip displacement and need for surgical intervention, the evidence regarding radiological characteristics is less clear [21,22].…”
Section: Introductionmentioning
confidence: 99%